1993
DOI: 10.1210/en.133.1.208
|View full text |Cite
|
Sign up to set email alerts
|

Chronic perifusion of rat islets with palmitate suppresses glucose- stimulated insulin release

Abstract: To test the hypothesis that the high circulating FFA levels in the diabetes of obesity could contribute to the altered dynamics of insulin secretion seen in that condition, insulin release was measured in isolated perifused rat islet cells, without or with added palmitate. Acutely, as in other systems, palmitate (1 mM) stimulated insulin release. Palmitate (1 mM) suppressed both first and second phase insulin release after 2, 3, or 4 h of perifusion, but not after 1 h. No significant effect was noted with 0.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
56
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 0 publications
5
56
0
1
Order By: Relevance
“…The deleterious effect of high glucose is well established [2,3], but increased NEFA at physiological glucose concentrations were also able to significantly alter GSIS and insulin content. These results are in accordance with previous studies [6,10,33], but argue against the hypothesis that increased glucose is a prerequisite for the deleterious effect of NEFA on betacell function [11,12,13,14]. We also found that in-action is, at least in part, mediated by modifications in gene expression [9,17].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The deleterious effect of high glucose is well established [2,3], but increased NEFA at physiological glucose concentrations were also able to significantly alter GSIS and insulin content. These results are in accordance with previous studies [6,10,33], but argue against the hypothesis that increased glucose is a prerequisite for the deleterious effect of NEFA on betacell function [11,12,13,14]. We also found that in-action is, at least in part, mediated by modifications in gene expression [9,17].…”
Section: Discussionsupporting
confidence: 92%
“…The marked increase in CPT-I expression induced by NEFA, and its negative correlation with GSIS suggest that CPT-I could exert a central role in the loss of beta-cell signal recognition induced by NEFA. Those results are concordant with the glucose fatty acid cycle reported in rat islets [6,7,10]. This hypothesis proposes that an increase in NEFA oxidation leads to a decrease in glucose metabolism in beta-cells, according to the Randle cycle observed in other tissues [40].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations